Fascial neuromodulation: an emerging concept linking acupuncture, fasciology, osteopathy and neuroscience - Gianluca Bianco (PAGEPress Publications, 2019)
According to Traditional Chinese Medicine "acupuncture is believed to restore the balance between Yin and Yang" and this can be understood in the Western medicine terminology as a "modulation of the equilibrium between parasympathetic and sympathetic activity". The vast majority of studies concerning the mechanisms of action of acupuncture have been conduct-ed on its influence on pain, and it has been proposed that acupuncture may indirectly relieve chronic pain by its effects on autonomic nervous system function. Several studies have shown that acupunc-ture recruits brain networks involved in the integration of multiple other brain functions: for example, the limbic-paralimbic-neocortical network, which plays a major role in modulating the affective di-mensions of pain processing and the integration of emotional, sensorimotor, autonomic and immuno-logical functions. It has been recently proposed that mechanical signaling through the connective tissue, along with transmission of the matrix deformation through the fascial system network, can explain the therapeutic effect of acupuncture. This model of acupunture, which involves the transduction of mechanical sig-nals through the connective planes and produces a secondary involvement of neurophysiological mechanism, appears to fit very closely to the ancient model. It is also compatible with the proposed neurophysiological explanation. Furthermore, it appears to be fruitful also in manual therapy ap-proaches. Drawing on the basis of the "Fascial network hypothesis of meridians", in which there is an overlap between the channels network described by Traditional Chinese Medicine and the newly-defined fas-cial system, I propose an intervention through a combination of acupoints that have been selected due to their relationship between "extaordinary acupuncture channels", the myofascial sequences de-scribed by Stecco, and the emotional and adaptive function as contemplated by a psychosomatic model used in posturology. This intervention is aimed at treating both stress and postural imbalance.